2012
DOI: 10.7473/ec.2012.47.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Properties of Polyolefin with Maleic Anhydride as a Functional Monomer

Abstract: ABSTRACT:Surface modification of macromolecules renders a progressive and favorable method to enhance the properties of polymeric materials and improves conductivity, wettability, stability, adhesion, antibacterial properties, etc. of polymeric surfaces without deterioration of the polymer bulk properties. Polyolefins such as polyethylene and polypropylene were grafted with maleic anhydride(MAH) as a functional monomer in solution. Evidence for grafting was shown with FTIR measurement. The grafting ratio was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…This is associated with the high number of free radicals, which may react with the PP and MHBP and so enhance FD. The same behavior has been observed for the functionalization of PP with MA in solution . PP‐ g ‐MHBPs prepared with 3.0 wt % (PP‐ g ‐MHBP1, PP‐ g ‐MHBP2 and PP‐ g ‐MHBP3) MHBP exhibited lower FD than those obtained with 9.0 wt % (PP‐ g ‐MHBP4, PP‐ g ‐MHBP5 and PP‐ g ‐MHBP6).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This is associated with the high number of free radicals, which may react with the PP and MHBP and so enhance FD. The same behavior has been observed for the functionalization of PP with MA in solution . PP‐ g ‐MHBPs prepared with 3.0 wt % (PP‐ g ‐MHBP1, PP‐ g ‐MHBP2 and PP‐ g ‐MHBP3) MHBP exhibited lower FD than those obtained with 9.0 wt % (PP‐ g ‐MHBP4, PP‐ g ‐MHBP5 and PP‐ g ‐MHBP6).…”
Section: Resultssupporting
confidence: 73%
“…Another study reported the functionalization of MA (3.0 wt %) in solution, using dicumyl peroxide (DCP) as an initiator (0.10–0.80 wt %); the FD values were between 0.27 and 0.34 wt % . PP was functionalized with MA in solution by employing benzoyl peroxide (BPO) as a catalyst (1.0 wt %); the proportions of MA employed were between 10 and 20 wt % and the FD values obtained were between 0.10 and 3.0 wt % …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] After the pioneer work of Minoura et al in 1969, 8,9 several researchers successfully grafted MAH groups onto iPP chains and analyzed their impact on the polymer properties. [10][11][12][13][14][15][16][17][18] Otherwise some authors studied the reaction of excess diamines in iPP-g-MAH systems and concluded that primary amines favor chain grafting. [19][20][21] More advanced workers analyzed on the influence of NH 2 :MAH molar ratio on the macromolecular architecture, the cross-link density, the semi-crystalline microstructure and the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%